Dual-Band Dielectric Resonator Antenna for C and X Band Application - Deepak Batra; Sanjay Sharma; Amit Kumar Kohli (International Journal of Antennas and Propagation)
The proposed technique combines a slot antenna and a dielectric resonator antenna (DRA) to effectively design a dual band dielectric resonant antenna without compromising miniaturization or its efficiency. It is observed that the resonance of the slot and that of the dielectric structure merged to achieve extremely wide bandwidth over which the antenna polarization and radiation pattern are preserved. Here the effect of slot size on the radiation performance of the DRA is studied. The antenna structure is simulated using two simulators (Ansoft HFSS and CST-Studio software). The simulated results are presented and compared with the measured results. This DRA has a gain of 6 dBi and 5.5 dBi at 6.1 and 8.3 GHz, respectively, 10 dB return impedance bandwidth of nearly 4% and 6% at two resonating frequencies and 98% efficiency has been achieved from the configuration. It is shown that the size of the slot can significantly affect the radiation properties of the DRA, and there are good agreements between simulation and measured results.